Counting the platelets: a robust and sensitive quantification method for thrombus formation - Claesson, Kjersti; Lindahl, Tomas L.; Faxälv, Lars (Thrombosis and Haemostasis, 2016)
Flow chambers are common tools used for studying thrombus formation in vitro. However, the use of such devices is not standardised and there is a large diversity among the flow chamber systems currently used, and also in the methods used for quantifying the thrombus development. It was the study objective to evaluate a new method for analysis and quantification of platelet thrombus formation that can facilitate comparison of results between research groups. Whole blood was drawn over a collagen patch in commercial Ibid or in-house constructed PDMS flow chambers. Five percent of the platelets were fluorescently labelled and z-stack time-lapse images were captured during thrombus formation. Images were processed in a Python script in which the number of platelets and their respective x-, yand z-positions were obtained. For comparison with existing methods the platelets were also labelled and quantified using fluorescence intensity and thrombus volume estimations by confocal microscopy. The presented method was found less sensitive to microscope and image adjustments and provides more details on thrombus development dynamics than the methods for measuring fluorescence intensity and thrombus volume estimation. The platelet count method produced comparable results with commercial and PDMS flow chambers, and could also obtain information regarding the stability of each detected platelet in the thrombus. In conclusion, quantification of thrombus formation by platelet count is a sensitive and robust method that enables measurement of platelet accumulation and platelet stability in an absolute scale that could be used for comparisons between research groups.
Keywords: Platelet aggregation; microfluidics; thrombosis; fluorescence microscopy; computer-assisted image processing